"Celebratio sursum ad Dominum": Priest and People at the Altar - Ryan, Fergus (Questions liturgiques, 2021)
The author considers whether there is an official, preferred directionality for the priest at the altar in the Ordinary Form of the Roman Rite of Mass. He examines the editions of the Roman Missal promulgated after Vatican II, comparing and contrasting the relevant details with those in the Roman Missals promulgated between 1570 and 1962. He reviews the few mentions during the Second Vatican Council of directionality at the altar, including those comments made during public sessions but rarely mentioned in the literature. He provides a brief study of the matter in the modern liturgical movement before the Council and in preparatory documents for the Council. Finally, he examines other liturgical books and directives following Vatican II, including directionality matters concerning the presidential chair. He concludes that versus populum is the official, preferred directionality, noting that the design of sanctuaries following the Council overlooks that altars are, theologically and in the architectural tradition, sursum ad Dominum, in spite of the helps offered within the preparatory documentation which emphasise that forgotten direction.